Posyandu cadre training in utilizing information systems to manage elderly medical record data - Hendra Rohman; Nur Ismiyati; Iramie Duma Kencana Irianto (Universitas Muhammadiyah Magelang, 2022)
Posyandu activities for the elderly are carried out regularly in RW 29 and RW 30 Padukuhan Tegalwaras, Sariharjo, Kapanewon Ngaglik, Sleman, Yogyakarta. Bougenvile Posyandu cadres carry out the process of recording medical record data on paper and books. Data that is difficult to read and unsustainable needs to be changed. The aim of this program is to train all posyandu cadres in managing elderly data through a web browser. The implementation method is an analysis of information system needs, counseling related to health information systems, technical training of equipment used, assistance in the use of information systems, monitoring and evaluating the results of all activities by analyzing the ability to use posyandu information systems every month. As a result, on the system there are main menus, namely registration, inspection, print reports, graphics, restore data, user data, my profile, materials, and activities. The existence of an information system for the elderly posyandu is able to increase the knowledge and skills of cadres in managing data using a web-based information system.